Location tracking activity to develop spatial concept understanding: Case study of grade 9 students in SMPN 1 Lembang - Pamungkas Totok Doyo; Ismail Jalu Rafli; Primananda Stefan; Fadillah Viola Gustia (E3S Web of Conferences)
In social science subjects for junior high school students, spatial themes cover a variety of topics, namely spatial interrelation and interdependence, spatial interaction, as well as interspace excellence and limitations. Spatial concept understanding will help students to attain Basic Competences (Kompetensi Dasar/KD), which in general is to understand, analyze, and explain how location and places affect patterns of human activities. The limitation of the lecture method on delivering spatial concepts became the background of this research. In order to improve student activities through scaffolded teaching, the activity of finding information through location tracking is implemented. To analyze the whole process, this research uses a qualitative experimental method. The study shows the increases in student participation during class session, formative test scores, and amount of time reduced in finding answers. The result of this research shows that Location Tracking Activity has increased students’ activity during the learning process, as well as motivation of learning. The experiment process resulted in the attainment of basic competencies in students’ learning process, as well as 40% increase in students participation during the class; 35% increase in cooperating with their classmates during discussion; and 40% increase in interacting with the teacher.